2016
DOI: 10.1111/cch.12327
|View full text |Cite
|
Sign up to set email alerts
|

No widening socioeconomic gap within a general decline in Swedish breastfeeding

Abstract: No increase in socioeconomic gap was detected within the general decline in Swedish breastfeeding. However, there are reasons to maintain and strengthen the overall breastfeeding supportive measures including extended support for vulnerable groups.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 25 publications
1
13
0
Order By: Relevance
“…An intervention study from Sweden revealed that professional breastfeeding support can affect the mothers`feelings for their infants and enjoyment of breastfeeding [29] which indicates the need of satisfactory professional support. e socioeconomic factors (age, education, perceived economy, and length of parental couple relationship) that are commonly reported to be associated with the duration of breastfeeding [48][49][50] were analysed within this study. Remarkably, in this study, none of the included socioeconomic factors were significantly correlated with neither the duration nor the enjoyment of breastfeeding.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…An intervention study from Sweden revealed that professional breastfeeding support can affect the mothers`feelings for their infants and enjoyment of breastfeeding [29] which indicates the need of satisfactory professional support. e socioeconomic factors (age, education, perceived economy, and length of parental couple relationship) that are commonly reported to be associated with the duration of breastfeeding [48][49][50] were analysed within this study. Remarkably, in this study, none of the included socioeconomic factors were significantly correlated with neither the duration nor the enjoyment of breastfeeding.…”
Section: Discussionmentioning
confidence: 99%
“…In a Swedish study examining breastfeeding until six months of age in a sample of 51-415 children, born between 2004 and 2011, the researchers found that the socioeconomic gap between the mothers' duration of breastfeeding had been narrowed, though it still existed. In that study, they hypothesised that the narrowed gap could be explained by the fact that highly educated women, who once started the trend of longer breastfeeding in Sweden during the 1980s and 1990s, now might be the first to follow a new trend of breastfeeding for a shorter time [50]. While the present study has a much smaller sample and therefore might not find small correlations, the results still suggest that it is unlikely that socioeconomic factors can explain much of what affects the mothers' experience of and the duration of breastfeeding in Sweden.…”
Section: Discussionmentioning
confidence: 99%
“…In Sweden, breastfeeding rates were lower for mothers with disposable incomes in the first three quartiles than in the last quartile [17]. Nonetheless, even though the breastfeeding rates are influenced by socioeconomic status, the decline cannot be explained by the widening socioeconomic gap [18].…”
Section: Introductionmentioning
confidence: 91%
“…A recent Swedish study found that rates of breastfeeding declined among women of all SEP groups (measured using education, marital status, or disposable income) between 2004-2010, though the differences between groups did not increase. 270 This study did not find a significant association between level of disposable income and the odds of breastfeeding at one…”
Section: Conclusion 82mentioning
confidence: 57%
“…week, four months, or six months, although education was significantly inversely associated with breastfeeding at each time point. 270 These results suggest that other factors beyond financial stress may be driving social differences in breastfeeding; given that, even in Sweden -a country with a generous welfare state, that can minimise the financial stress experienced due to child-rearing -educational differences in breastfeeding remained.…”
Section: Conclusion 82mentioning
confidence: 92%